Quality of life in relationship with experience of decay in patients of the dental clinic of the San Martin de Porres University of Chiclayo - More – Neyra, Katherine (2015)
Martin de Porres University - Chiclayo Branch, between the months of March and April 2015. Materials and Methods. This study hascharacteristics of a non-experimental and quantitative study, with descriptive correlational and cross-sectional design. 110 adultspatients were evaluated, through the use of stomatology sheets and the quality of life questionnaire WHOQOL - Bref previously validated.The Spearman correlation coef